Increasing The Knowledge of Disaster Resilient Generation Youth on Disaster Mitigation at MAS Darul Hikmah Aceh Besar: Peningkatan Pengetahuan Remaja Generasi Tangguh Bencana Tentang Mitigasi Bencana Di MAS Darul Hikmah Aceh Besar - Asiah, Nur; Asnah Sitohang, Nur; Suryani Oktari, Rina (Jukeshum: Jurnal Pengabdian Masyarakat, 2025)
Floods that have occurred in Baitussalam District have been going on for a long time, especially in Gampong Kahju. The goal of achieving SDGs in this PkM is handling climate change (Climate action). The purpose of this research is to identify youth knowledge through the GENTAB program regarding disaster mitigation at MAS Darul Hikmah, Kahju Village, Aceh Besar. The research design that has been used is descriptive. The sample collection technique used was purposive sampling. The research results showed that respondents' knowledge was good (25%), sufficient (36.67%) and poor (38.33%). This research proves that health education about disaster mitigation still needs to be carried out to increase youth knowledge and preparedness. in facing disasters.